2012
DOI: 10.1111/j.1468-3083.2012.04547.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of drug‐induced hypersensitivity syndrome treated without systemic corticosteroids

Abstract: It might be unnecessary to give systemic corticosteroids immediately to all patients suspected of having DIHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 15 publications
(47 reference statements)
3
24
2
5
Order By: Relevance
“…It might be speculated that the delay in these cases is related to reactivation of HHV6. It is also interesting to note that the median number of days between the first day of drug administration and the first day of onset of symptoms of fever or rash in this series ( n = 28) is 9 (IQR 4·5–14·5), which is similar to the median number of days in the study of Uhara et al . of 10·5 (IQR 4–16).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It might be speculated that the delay in these cases is related to reactivation of HHV6. It is also interesting to note that the median number of days between the first day of drug administration and the first day of onset of symptoms of fever or rash in this series ( n = 28) is 9 (IQR 4·5–14·5), which is similar to the median number of days in the study of Uhara et al . of 10·5 (IQR 4–16).…”
Section: Discussionsupporting
confidence: 82%
“…Among those negative for HHV6, 20 patients were treated with systemic corticosteroids (median total dose 5 mg kg À1 , range 1-16) and five patients were managed with supportive therapy alone. All four patients positive for HHV6 were treated with systemic corticosteroids (median total dose 6Á5 mg kg À1 , range [2][3][4][5][6][7][8][9][10][11][12][13][14]. Systemic corticosteroids were administered either intravenously or orally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported autoimmune disease occurrence and/or autoantibody production during a period of several months to years after the resolution of DRESS/DIHS, including diabetes mellitus type 1, lupus erythematosus, Hashimoto thyroiditis, enteropathy, sclerodermiform lesion‐type graft‐versus‐host disease and bullous pemphigoid . In the present study, none of the definite cases of DRESS/DIHS had any autoimmune disease detected before 2012.…”
Section: Discussioncontrasting
confidence: 42%
“…Uhara et al reported on 12 patients with DiHS who received hydration with or without topical steroids [120]. All of these 12 patients recovered well, without complications of infections, within 7 to 37 days after the withdrawal of the inciting drugs.…”
Section: Treatmentsmentioning
confidence: 99%